2021
DOI: 10.1097/tp.0000000000003619
|View full text |Cite
|
Sign up to set email alerts
|

Torque Teno Virus Load Is Associated With Subclinical Alloreactivity in Kidney Transplant Recipients: A Prospective Observational Trial

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 15 publications
3
53
1
Order By: Relevance
“…Various studies have investigated the performance of TTV kinetics to predict acute rejection after KT, [54][55][56][73][74][75] LT 57,87 and LuT. 59,60,67 In a single-center study with 63 KT recipients, Solis et al found that those with TTV DNA load below 3.4 log 10 copies/ml at the time of transplantation or below 4.2 log 10 copies/ml by month 1 exhibited a 6-to-7-fold increase in the risk of graft rejection (mainly TCMR) within the next two years.…”
Section: Association Between Ttv Load and Acute Graft Rejectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have investigated the performance of TTV kinetics to predict acute rejection after KT, [54][55][56][73][74][75] LT 57,87 and LuT. 59,60,67 In a single-center study with 63 KT recipients, Solis et al found that those with TTV DNA load below 3.4 log 10 copies/ml at the time of transplantation or below 4.2 log 10 copies/ml by month 1 exhibited a 6-to-7-fold increase in the risk of graft rejection (mainly TCMR) within the next two years.…”
Section: Association Between Ttv Load and Acute Graft Rejectionmentioning
confidence: 99%
“…In addition, various studies have reported a direct correlation between TTV DNA loads and trough CNI levels over the previous weeks, 58,59 although this finding has not been consistently replicated 54,57,60,69 . An inverse correlation between the time interval since transplantation and viral load has been observed in studies based on prevalent, rather than incident, KT recipients 54–56,72–75 …”
Section: Torque Teno Virus In Solid Organ Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines, chemokines [15,16] ImmunoKnow-Assay [17][18][19][20][21] TorqueTenoVirus [16,[22][23][24][25][26][27][28][29] Virus-specific T cells [30][31][32][33][34] Ahlenstiel-Grunow and Pape Molecular and Cellular Pediatrics (2021) 8:8…”
Section: Methods Studiesmentioning
confidence: 99%
“…TTV load increases under immunosuppressive therapy, and replication is inversely correlated with the number and function of T cells [22][23][24]. Several studies reported an association of TTV load with the post-transplant presence of infections or rejections [16,[25][26][27], and recently, an observational trial confirmed that high TTV load is related to an increased risk of post-transplant infections and decreased risk of rejections after kidney transplantation [28]. However, in liver-transplanted children, it was reported that TTV replication is influenced not only by immune status but also by viral coinfection resulting in lower TTV load in case of hepatitis E virus infection [29].…”
Section: Methods Studiesmentioning
confidence: 99%